2007
DOI: 10.1021/nl062989e
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Local Photocurrents in Polymer/Fullerene Solar Cells with Photoconductive Atomic Force Microscopy

Abstract: The performance of organic solar cells is highly dependent on film morphology. However, directly correlating local film structures with device performance remains challenging. We demonstrate that photoconductive atomic force microscopy (pcAFM) can be used to map local photocurrents with 20 nm resolution in donor/acceptor blend solar cells of the conjugated polymer poly[2-methoxy-5-(3',7'-dimethyloctyl-oxy)-1,4-phenylene vinylene] (MDMO-PPV) with the fullerene (6,6)-phenyl-C61-butyric acid methyl ester (PCBM) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
263
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(274 citation statements)
references
References 45 publications
8
263
1
2
Order By: Relevance
“…14,15,17 Indeed, there is experimental evidence, which shows that the blend morphology can significantly affect mobility in the manner we propose, for example, 28,29 and further data that local morphology affects local charge transport. 8 Drift-diffusion modeling has shown that changes in the local mobility of one order of magnitude can give rise to significant changes in SCL diode and PV device performance. It is shown that the sequence of the layers with different mobilities makes a profound difference to the current the SCL diode carries, and in turn, the effective mobility derived.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,17 Indeed, there is experimental evidence, which shows that the blend morphology can significantly affect mobility in the manner we propose, for example, 28,29 and further data that local morphology affects local charge transport. 8 Drift-diffusion modeling has shown that changes in the local mobility of one order of magnitude can give rise to significant changes in SCL diode and PV device performance. It is shown that the sequence of the layers with different mobilities makes a profound difference to the current the SCL diode carries, and in turn, the effective mobility derived.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…5 However, while these techniques broadly control the domain size, crystallinity, or packing of the components of the BHJ, these characteristics of the blend morphology are not uniform throughout the film. Indeed, studies of the structure of polymer-polymer, 3,6,7 polymer-fullerene, [8][9][10] and polymernanocrystal 11 blends show hierarchies of phase separation and vertical variations in the blend morphology. How this local variation in blend morphology affects the local mobility of carriers, and in particular the PV performance, is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Current can in this way flow through the material, from the biased lateral contact to the movable metal-coated scanning probe tip [19]. In a similar configuration, named Photoconductive Atomic Force Microscopy (PC-AFM) [69], a light source is additionally used to excite the sample, so that the resulting photocurrent is measured by the AFM probe. For electrical measurements, preventing probe-induced artifacts is very important.…”
Section: Electrical Modesmentioning
confidence: 99%
“…Furthermore, it is apparently clear that the production cost can be severely reduced by the utilization of the abundant inorganic materials and a low production cost film fabrication techniques such as spin casting, electrochemical deposition and screen printings unlike the use of expensive and complex film forming techniques such as CVD, electron beam and MOCVDs [9]. Since the solution processable organic solar cells are extensively studied and highly promising next generation photovoltaics, however, the generation of Frenkel type excitons at the donor/acceptor interface needed a larger surface area and excellent contacts at the film interfaces [10]. Moreover, in organic solar cells the effective harvesting of generated geminate pairs at electrodes also posing limitations to the higher efficiencies due to slow charge carrier mobility's (~10 -4 cm 2 V -1 c -1 ) of organic layers towards the electrode surface, however inorganic type solar cells possess strong chemical stability, high mobility and strong intrinsic charge carriers which make them choice for large scale manufacturing [11].…”
Section: Introductionmentioning
confidence: 99%